PENINGKATAN KEMAMPUAN MENULIS PERCAKAPAN MELALUI METODE LATIHAN SISWA KELAS IV SD NEGERI 003 BANGKINANG KECAMATAN BANGKINANG KABUPATEN KAMPAR - Novianti Erliasari Novianti Erliasari; M. Nur Mustafa M. Nur Mustafa; Mangatur Sinaga Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study was conducted because of the students' writing ability is low. It can be seen (1) student mastery of the material is still less taught, it can be seen from the results of the daily tests carried out and the value of the majority of the semester students are below the Minimum Criteria for completeness (KKM) is 35.3% while that, which should KKM in the classroom at least 70%, (2) students are less active in the subjects presented, it is seen from the activities of children who tend to just quietly listening to the teacher deliver material without responding, and (3) low ability students in writing a text conversation simple in grade IV elementary School District 003 Bangkinang Bangkinang District of Kampar. Of the 34 students, only 12 people who can write a good text conversation with. The method used in this study is action research. The results showed an increase in the teaching of writing essays conversation with the application of training methods. Based on the research results, it could be concluded towards this research is to improve the ability to write a conversation with the training methods Elementary School fourth grade students Bangkinang 003 Bangkinang District of Kampar district. Average student at the beginning of the test were categorized with an average value of 63.2, and in the first cycle increased to 71.8 with the high category, while the second cycle of the average ability of students categorized as good with an average value of 89.4. completeness in terms of number of students who completed the student reaches 94.12% or 32 of 34 students. From the data on the increase in capacity and the number of students who achieve mastery KKM then exercise techniques proven to improve the ability to write the conversation. Thus the research hypothesis that reads "Improved Ability to write conversations with students training methods fourth grade 003 State Bangkinang Bangkinang District of Kampar district" may be "acceptable".Keywords: Conversational Writing Ability, Drill Methods